Kapitalismekritiske teaterdokumentarismer - Lauenstein Led, Jens Christian (Peripeti, 2014)
The article seeks to argue that it may be fruitful to observe certain tendencies to critique of capitalism through documentary strategies in contemporary theatre in the light of the theatre and theories of Erwin Piscator, defending the thesis, that the similarities between the two are larger than what is typically assumed. Three theatrical art works are analyzed: Marat – was ist aus unser Revolution geworden? by director Volker Lösch; Das Himbeerreich by Andres Veiel, and Karl Marx: Das Kapital, erster band by the group Rimini Protokoll. All three are read as piscatorian, in as far as it is shown, how they in different manners return to his concepts, all though the political aspect seems to have been sliding from an insisting hope, to a desperate utopia.